ANALISIS PERTUMBUHAN EKONOMI, DAN INDEKS HARGA SAHAM GABUNGAN DI INDONESIA - Juita, Popy Citra; Wardi, Yunia; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2014)
This study aims to analyze (1) Influence of investment, inflation and the exchange rate of the economic growth in Indonesia. (2) Effect of exchange rate, money supply, interest rates and economic growth SBI on stock prices in Indonesia. This study uses a simultaneous equation model analysis tools using Indirect Least Squares (ILS). The study concluded that (1) investment and exchange rate jointly significant effect on economic growth in Indonesia, while inflation is not significant and negative effect on economic growth in Indonesia. (2) the exchange rate, money supply, interest rate SBI and economic pertunbuhan significant effect on stock price index in Indonesia. This study only uses five macroeconomic variables, so that further research needs to find other macroeconomic variables that presumably affect the economic growth and stock prices. Keywords:investment,inflation,exchange rate,money supply,interest rate,economic growth and stock prices